Dampak keberadaan objek wisata Athaya Garden terhadap perekonomian masyarakat di Dusun Senamat Kecamatan Pelepat Kabupaten Bungo - Muhammad Safri; Jaya Kusuma Edy; Salshabila Berliani (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to: 1) Knowing and analyzing the characteristics of the business community around the Athaya Garden Dusun Senamat, 2) Knowing and analyzing people's income before and after the Athaya Garden tourism object in Senamat Hamlet, and 3) Knowing and analyzing the effect of age, education level, length of working hours, and operating capital on the income of business actors around the Athaya Garden Dusun Senamat tourist attraction. The method used in this research is descriptive quantitative, with primary data obtained through interviews with 30 business people around the Athaya Garden tourist attraction. Based on the results of the different test with the Wilcoxon Signed t-test, it shows that there is an increase in the income of business actors after the Athaya Garden tourist attraction in Dusun Senamat. Based on the results of multiple linear regression, simultaneously age, education level, length of working hours, and operating capital have a significant effect on the income of business actors. Partially, operational capital affects the income of business actors, for the age variable that negatively and partially affects the income of business actors. Meanwhile, the variables of education level and length of working hours partially have no effect on the income of business actors.